2013
DOI: 10.1111/fcp.12045
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of cAMP agonist on ameliorative function of PKA inhibitor in morphine‐dependent mice

Abstract: The present study shows interactive effects of bucladesine (db-cAMP) as a cyclic adenosine monophosphate (cAMP) agonist and H-89 as a protein kinase A (PKA) inhibitor on naloxone-induced withdrawal signs in morphine-dependent mice. Animals were treated subcutaneously with morphine thrice daily with doses progressively increased from 50 to 125 mg/kg. A last dose of morphine (50 mg/kg) was administered on the 4th day. Several withdrawal signs were precipitated by intraperitoneal (i.p.) administration of naloxone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
(98 reference statements)
1
9
0
Order By: Relevance
“…Previous studies have demonstrated that DFosB isoforms are responsible for drug tolerance, craving, and withdrawal syndrome [3,18,19,22]. Interestingly, alterations in Fos gene expression are also implicated in mediating certain pathological processes such as cellular apoptosis and oxidative stress [32]. We can relate these findings to our study in a way that varying dosage regimens of morphine such as increasing dosage intervals, decreasing dosage, and irregular administration intervals can alter DfosB gene expression and this can modulate the behaviors in withdrawal syndrome.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previous studies have demonstrated that DFosB isoforms are responsible for drug tolerance, craving, and withdrawal syndrome [3,18,19,22]. Interestingly, alterations in Fos gene expression are also implicated in mediating certain pathological processes such as cellular apoptosis and oxidative stress [32]. We can relate these findings to our study in a way that varying dosage regimens of morphine such as increasing dosage intervals, decreasing dosage, and irregular administration intervals can alter DfosB gene expression and this can modulate the behaviors in withdrawal syndrome.…”
Section: Discussionmentioning
confidence: 53%
“…In contrary, some long acting drugs appear to cause less significant side effects while manipulating the re-uptake of specific neurotransmitters or amino acids levels in brain [20,31]. Interestingly, alterations in Fos gene expression are also implicated in mediating certain pathological processes such as cellular apoptosis and oxidative stress [32]. Biochemically modified isoforms of DFosB accumulate within the some parts of brain regions after repeated drug exposure, while other Fos family members remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…[525354] Interestingly, Alterations in Fos gene expression are also implicated in mediating certain destructive effects such as apoptosis and oxidative stress in cells. [55] Based on mentioned result and studies we can discuss that by altering dosage regimen, such as our protocol, probably the ΔFosB isoforms, which involved in addiction behavior, were changed and addiction relative behavior such as anxiety, depression, and cognition impairment were modulated.…”
Section: Discussionmentioning
confidence: 97%
“…We found that naloxone precipitated five cardinal signs of opiate withdrawal—jumping, forepaw tremor, wet-dog shakes, rearing, and defecation [Gabra et al ., 2008; Seyedi et al ., 2014; Wu et al ., 2014]—in morphine-dependent mice. The frequency of all five withdrawal signs was reduced by HBO 2 treatment, although the reduction in only four endpoints was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…on day 5. The dose schedule was derived from the scientific literature [Seyedi et al, 2014], but the t.i.d. schedule for three days was lengthened to b.i.d.…”
Section: Methodsmentioning
confidence: 99%